2018
DOI: 10.3390/v10100556
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Critical Functions of Long Non-Coding RNAs and mRNAs in Rhabdomyosarcoma Cells and Mouse Skeletal Muscle Infected by Enterovirus 71 Using RNA-Seq

Abstract: Enterovirus 71 (EV71) is the main pathogen of severe hand-foot-mouth disease (HFMD). Long non-coding RNAs (lncRNAs) are recognized as pivotal factors during the pathogenesis of viral infection. However, the critical functions of lncRNAs in EV71–host interactions have not been characterized. Here, for the first time, we performed global transcriptome analysis of lncRNA and mRNA expression profiles in EV71-infected human rhabdomyosarcoma (RD) cells and skeletal muscle of mice using second-generation sequencing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Overexpression of MYOF has been associated with many cancers in humans, including breast cancer, lung cancer, and pancreatic cancer, and is shown to promote tumorigenesis, tumor cell motility, proliferation, migration, and metastasis [32][33][34]. Furthermore, other studies had reported up-regulation or down-regulation of TMEM156, ELOVL5, KIF23, AMPD3, CCNB1, CENPE, UBE2C, NXPE3, and PDE4DIP to be associated with numerous types of cancers in humans, such as breast cancer, ovarian cancer, non-small cell lung cancer, clear cell renal cell carcinoma, stomach cancer, colorectal cancer, esophageal cancer, pancreatic cancer, hepatocellular cancer, lung cancer, and prostate cancer [35][36][37][38][39][40][41][42][43][44][45]. Our results were consistent with the previous findings that indicated DEGs to possibly have great implication in tumor/cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of MYOF has been associated with many cancers in humans, including breast cancer, lung cancer, and pancreatic cancer, and is shown to promote tumorigenesis, tumor cell motility, proliferation, migration, and metastasis [32][33][34]. Furthermore, other studies had reported up-regulation or down-regulation of TMEM156, ELOVL5, KIF23, AMPD3, CCNB1, CENPE, UBE2C, NXPE3, and PDE4DIP to be associated with numerous types of cancers in humans, such as breast cancer, ovarian cancer, non-small cell lung cancer, clear cell renal cell carcinoma, stomach cancer, colorectal cancer, esophageal cancer, pancreatic cancer, hepatocellular cancer, lung cancer, and prostate cancer [35][36][37][38][39][40][41][42][43][44][45]. Our results were consistent with the previous findings that indicated DEGs to possibly have great implication in tumor/cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the most significant KEGG pathways were associated with cancer pathways, metabolic pathways, viral infection pathways, Ras and Rap 1 signaling pathways, and so on. Li et al [36] had reported genes from rhabdomyosarcoma to be enriched in many pathways, such as metabolism, viral infectious diseases, immune system, signal transduction, HTLV-1 infection, herpes simplex virus infection, Epstein-Barr virus infection, and cancer. GO terms in the present study indicated BLV infection to mainly modify host metabolism, cellular components, signal transduction, and cell proliferation, and mRNA profile in milk EVs reflected these modifications.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs) affecting host responses [38][39][40][41][42][43][44], the study of interactions between pathogens and lncRNAs has just recently begun. Many lncRNAs have been shown to be differentially expressed in myeloid and non-myeloid cells during infection with pathogens such as Mycobacterium tuberculosis [45,46], Escherichia coli [47], Rabies virus [48] and fungi [49] in humans, and Enterovirus 71 [50] and Toxoplasma gondii [51] in mouse. However, the signaling pathways or cellular events they regulate remain poorly understood.…”
Section: Host-derived Lncrnasmentioning
confidence: 99%
“…Although Yin et al [12] reported that 2,990 lncRNAs are upregulated and 1,876 lncRNAs are downregulated in EV71-infected RD cells compared with mock groups by using lncRNA microarray analyses, there is still no report on how lncRNAs play the functional role during EV71 infection [14]. In our study, we found that lncRNA-AK097647 expression was increased during EV71 infection, and this might be a positive feedback mechanism which lncRNA-AK097647 could contribute to EV71 replication in human RD cells.…”
Section: Discussionmentioning
confidence: 99%